Kontribusi Program Irigasi Perpompaan terhadap Ketahanan Pangan Masyarakat di Kabupaten Tana Toraja - Idam Hanafi K; La Sumange; Herman Nursaman; Helda Ibrahim (SENTRI: Jurnal Riset Ilmiah, 2025)
This study analyzes the contribution of the pump-based irrigation program to improving food security in Tana Toraja Regency, focusing on the dimensions of availability, access, and stability. The research was conducted in Mengkendek District, where pump irrigation has become a major strategy for addressing water shorthages in highland agricultural systems. A descriptive qualitative approach supported by quantitative data using a Likert-scale questionnaire was employed. Twenty-one farmers representing seven farmer groups participated in the study. The results show that pump irrigation significantly enhances food availability by increasing production, cropping frequency, and cultivated land area. Food access improved through higher income and greater purchasing power, enabling more diverse and nutritious food consumption.  Food stability also increased, supported by more consistent production throughout the year, although challenges such as pump damage, fuel costs, and topographical barriers remain. Overall, pump-based irrigation contributes substantially to strengthening household food security; however, sustained support through technical assistance, institutional strengthening, and operational cost management is needed to ensure long-term program sustainability.